2012
DOI: 10.1101/gr.146357.112
|View full text |Cite
|
Sign up to set email alerts
|

Mapping genomic hotspots of DNA damage by a single-strand-DNA-compatible and strand-specific ChIP-seq method

Abstract: Spontaneous DNA damage may occur nonrandomly in the genome, especially when genome maintenance mechanisms are undermined. We developed single-strand DNA (ssDNA)-associated protein immunoprecipitation followed by sequencing (SPI-seq) to map genomic hotspots of DNA damage. We demonstrated this method with Rad52, a homologous recombination repair protein, which binds to ssDNA formed at DNA lesions. SPI-seq faithfully detected, in fission yeast, Rad52 enrichment at artificially induced double-strand breaks (DSBs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 64 publications
1
32
0
Order By: Relevance
“…Indeed we have previously observed a substantial increase in Rad52 foci in dcr1 Δ cells as compared to WT (Zaratiegui et al, 2011), however the total level of Rad52 remains unchanged (data not shown), indicating that the Rad52 pool is limited. Rad52 nucleation occurs at sites of DNA damage during S-phase and subsequently spreads from the stall site (Zhou et al, 2013). To determine the precise location of replication stalling within rDNA we synchronized cells and performed Rad52 ChIP in S-phase.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed we have previously observed a substantial increase in Rad52 foci in dcr1 Δ cells as compared to WT (Zaratiegui et al, 2011), however the total level of Rad52 remains unchanged (data not shown), indicating that the Rad52 pool is limited. Rad52 nucleation occurs at sites of DNA damage during S-phase and subsequently spreads from the stall site (Zhou et al, 2013). To determine the precise location of replication stalling within rDNA we synchronized cells and performed Rad52 ChIP in S-phase.…”
Section: Resultsmentioning
confidence: 99%
“…1b). After washing, bead-bound ssDNAs are unidirectionally ligated to a bridge adapter 18 . Adapter-ligated, bead-bound ssDNA fragments are then subjected to nested PCR to incorporate a barcode sequence necessary for de-multiplexing (Fig.…”
Section: Overview Of the Lam-htgts Methodsmentioning
confidence: 99%
“…This improved method - LAM-HTGTS 6 - incorporates LAM-PCR 16,17 , bridge adapter ligation 18 , and a customized algorithm to fully characterize sequence reads with respect to the bait DSB employed. LAM-PCR employs a single primer to directly amplify bait-prey junctions from genomic DNA and generate single-stranded DNA (ssDNA) products with diverse ends 16,17 (Fig.…”
Section: Development Of Lam-htgtsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations of both HNH nuclease and RuvC catalytic domains (DM-Cas9-CV) abolished the cleavage activity (Supplementary information, Figure S1A, lane5). We performed chromatin immunoprecipitation using high affinity nanobody for the Venus protein (GBP) [13]. Cas9-CV was significantly enriched in the emx1 locus but not control egfa-t1 locus in an sgRNA-dependent manner, while DM-Cas9-CV showed a greatly enhanced binding in comparison with Cas9-CV ( Figure 1B and Supplementary information, Figure S1E).…”
mentioning
confidence: 99%